2008
DOI: 10.2535/ofaj.85.57
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphological study on the lingual papillae and their connective tissue cores in rabbits

Abstract: Summary:The morphological structure of the lingual papillae and their connective tissue cores (CTC) in a rabbit were studied using LM and SEM and were compared to that of other animal species. Externally, the filiform papillae distributed on the anterior surface of the dorsal tongue were short and conical with a round base and had a flat area on their anterior upper half. The CTC of the conical filiform papillae had a roughly triangular plate-like structure with a round top. Several small round protrusions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 31 publications
7
46
0
10
Order By: Relevance
“…The lingual median prominence was a characteristic feature in some mammals, which agree with our observation in New Zealand white rabbit tongue, and in; bank vole (Jackowiak & Godynicki, 2005), rabbit (Nonaka et al, 2008) and herbivorous artiodactylas (Zheng & Kobayashi, 2006), while omnivorous artiodactylas (pig) and carnivores animals not have a lingual prominence (Emura et al, 2006;Kumar & Bate, 2004). While (Pastor et al, 1993) in common European bat reported that there was a prominent of intermolar tubercle, moreover, molossid bats have a prominent mid-dorsal lobe as noted by Gregorin (2003), but Emura et al (2001b), Jackowiak et al (2009), Gregorin and Mqokeli & Downs (2012) reported that, there is no typically intermolar tubercle in all bats, while our study in the Egyptian fruit bat noted that, the characteristic feature of the dorsal surface of the middle part of tongue is the presence of a shallow intermolar tubercle, located close to the posterior half area of the tongue.…”
Section: Discussionsupporting
confidence: 91%
“…The lingual median prominence was a characteristic feature in some mammals, which agree with our observation in New Zealand white rabbit tongue, and in; bank vole (Jackowiak & Godynicki, 2005), rabbit (Nonaka et al, 2008) and herbivorous artiodactylas (Zheng & Kobayashi, 2006), while omnivorous artiodactylas (pig) and carnivores animals not have a lingual prominence (Emura et al, 2006;Kumar & Bate, 2004). While (Pastor et al, 1993) in common European bat reported that there was a prominent of intermolar tubercle, moreover, molossid bats have a prominent mid-dorsal lobe as noted by Gregorin (2003), but Emura et al (2001b), Jackowiak et al (2009), Gregorin and Mqokeli & Downs (2012) reported that, there is no typically intermolar tubercle in all bats, while our study in the Egyptian fruit bat noted that, the characteristic feature of the dorsal surface of the middle part of tongue is the presence of a shallow intermolar tubercle, located close to the posterior half area of the tongue.…”
Section: Discussionsupporting
confidence: 91%
“…Since the G. microtarsus presents three vallate papillae, as reported in D. virginiana (MARTINEZ et al, 1998) and D. marsupialis , this characteristic is due to the fact that these animals belong to the same family Didelphidae (ORR, 1986). On the other hand, D. albiventris (MARTINEZ et al, 1998) has only two vallate papillae.…”
Section: Discussionmentioning
confidence: 75%
“…The types of lingual papillae found in G. microtarsus differ from those other mammalian, such as Nasua nasua (SOUZA et al, 2012), Oryctolagus cuniculus (NONAKA et al 2008), Felis catus (CHAMORRO et al, 1987) and Callithrix penicillata (BRANCO et al 2,012) with only acute filiform papillae. In the case of F. catus, and Kerodon rupestris (SANTOS et al, 2015) foliate papillae have also been described (CHAMORRO et al 1987).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another important organ of digestory apparatus is the tongue, in which, different types of functional lingual papillae (WITT; REUTTER, 1997;BRANCO et al, 2011BRANCO et al, , 2012MANÇANARES et al, 2012) KOBAYASHI, 2008). The aim of this study was describe the morphological characteristics of the tongue of K. rupestris, providing more data for future researches.…”
Section: Introductionmentioning
confidence: 99%